MEASUREMENT MODEL: INTERESTS OF BUYING A SAMSUNG BRAND SMARTPHONE WITH CELEBRITY ENDORSER AS AN ANTESEDENT VARIABLES IN THE ERA OF COVID-19 - Ramdani Bayu Putra; Nandan Limakrisna; Hasmaynelis Fitri (Dinasti International Journal of Education Management And Social Science, 2020)
The occurrence of the Covid-19 Pandemic around the world has had an impact on changing consumer patterns and behavior. This study aims to analyze the impact of price on the buying interest of Samsung smartphones with Celebrity endorsers as an antecedent variable. The sample in this study were 98 students of the Putra Indonesia University YPTK Padang. This study uses structural equation modeling (SEM) with SmartPLS 3 as an analysis tool. The results of the study found that celebrity endorser is a factor that influences price and buying interest. Meanwhile, the price does not influence buying interest, nor does it play a role in strengthening the influence of Celebrity endorsers on buying interest. For this reason, producers must improve the quality of competitive prices while also maintaining the use of celebrity endorsers in supporting the marketing of their products.